1995
DOI: 10.1007/bf00169087
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of CYP2A5 expression by porphyrinogenic agents in mouse liver

Abstract: Coumarin 7-hydroxylase (COH) activity is catalyzed by the Cyp2a-5 gene product (CYP2A5 enzyme) in mice. Mouse hepatic CYP2A5 expression is often increased in conditions in which other P450 forms are repressed, e.g. after the administration of heavy metals and other toxic agents known to affect cellular heme balance. In this study, the effect of various porphyrinogenic chemicals on the expression CYP2A5 and the key enzymes in heme metabolism was studied. Administration of single doses of griseofulvin (1000 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
3
17
2
Order By: Relevance
“…Ratanasavanh et al (1996) also found that the metabolic rate of coumarin decreases in primary hepatocyte cultures from both man, rat and mice during the first 24 hr in culture. In the present study the same decrease was seen in cultures exposed to pyrazole, although pyrazole has been reported to be an inducer of coumarin 7-hydroxylase activity catalyzed by CYP2A5 in mouse primary hepatocytes (Kojo et al 1998) and in mouse livers after in vivo treatment with pyrazole (Salonpää et al 1995). Rifampicin did not induce the coumarin 7-hydroxylase activity either.…”
Section: Discussionsupporting
confidence: 74%
“…Ratanasavanh et al (1996) also found that the metabolic rate of coumarin decreases in primary hepatocyte cultures from both man, rat and mice during the first 24 hr in culture. In the present study the same decrease was seen in cultures exposed to pyrazole, although pyrazole has been reported to be an inducer of coumarin 7-hydroxylase activity catalyzed by CYP2A5 in mouse primary hepatocytes (Kojo et al 1998) and in mouse livers after in vivo treatment with pyrazole (Salonpää et al 1995). Rifampicin did not induce the coumarin 7-hydroxylase activity either.…”
Section: Discussionsupporting
confidence: 74%
“…The increased expression of Cyp2a4 observed here may be a cross hybridiation with Cyp2a5 known to be increased in expression during the development of liver injury and hepatocarcinomas (Camus-Randon et al 1996;Knasmuller et al 1997;Salonpaa et al 1995;Wastl et al 1998) and is also induced directly by porphyrinogenic agents (Salonpaa et al 1995). The most highly upregulated Cyp genes in this set, Cyp2b9, Cyp2b10, and Cyp2b13, were increased in expression up to 100-fold.…”
Section: Toxicogenomics | Gant Et Alsupporting
confidence: 49%
“…The latter has been associated with porphyria, liver injury, and hepatic tumors. [33][34][35] Western blotting confirmed the marked presence of CYP2A5 protein in livers of 26-week mice and hepatic adenoma tissue (Figure 4e). Changes in gene expressions associated with hepatocyte bile acid up-take, lymphocyte infiltration, remodeling, cirrhosis, and proliferation in older mice were mainly significantly less or absent in the 4-week-old mice com- Values represent means Ϯ of three to five mice.…”
Section: Modulation Of Expression With Agementioning
confidence: 64%